2023
DOI: 10.1039/d3ew00277b
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of enveloped and non-enveloped viruses to ultraviolet light-emitting diode (UV-LED) irradiation and implications for virus inactivation mechanisms

Abstract: Ultraviolet (UV) light-emitting diode (UV-LED), a disinfection technology, efficiently inactivates pathogens in water. However, the assessment of UV-LED treatment and the mechanisms of UV inactivation on viruses (especially enveloped viruses)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The viruses used in this study have different genomic properties, which may have a large impact on the rate of solar inactivation. Properties like a longer genome, an ssRNA genome structure (versus dsRNA), a monopartite genome (versus a segmented genome), , and a greater count of adjacent pyrimidine bases ,,, were previously suggested in UVC studies to be associated with larger decay rate constants. Generally, the genomic properties and corrected decay rate constants of the viruses we tested in this study follow the patterns previously suggested by the UVC studies: (1) Phi6 and MHV have larger genomes and larger corrected decay rate constants compared to MS2.…”
Section: Discussionmentioning
confidence: 96%
“…The viruses used in this study have different genomic properties, which may have a large impact on the rate of solar inactivation. Properties like a longer genome, an ssRNA genome structure (versus dsRNA), a monopartite genome (versus a segmented genome), , and a greater count of adjacent pyrimidine bases ,,, were previously suggested in UVC studies to be associated with larger decay rate constants. Generally, the genomic properties and corrected decay rate constants of the viruses we tested in this study follow the patterns previously suggested by the UVC studies: (1) Phi6 and MHV have larger genomes and larger corrected decay rate constants compared to MS2.…”
Section: Discussionmentioning
confidence: 96%